Evidence-based nursing home care for a patient with stage IV non-small cell lung cancer with coexisting diabetes mellitus - Chmielowska, Bożena; Dziubaszewska, Renata; Hajdon, Aleksandra; Makowicz, Dawid (Nursing in the 21st Century, 2022)
EVIDENCE-BASED NURSING HOME CARE FOR A PATIENT WITH STAGE IV NON-SMALL CELL LUNG CANCER WITH COEXISTING DIABETES MELLITUSIntroduction. Lung cancer is one of the most common malignant neoplasms in humans, while type 2 diabetes is a common civilization disease of the 21st century.Aim. The aim of the study was to present the role of a nurse in caring for a patient with advanced lung cancer and coexisting type 2 diabetes.Material and methods. The study used the case study method and literature analysis, as well as the following research techniques: interview, observation, document analysis, measurement, physical examination. Also, 15 scales were used to assess the patient’s health.Results. Nursing care for a patient with lung cancer and diabetes was focused mainly on preventing complications and disease progression, and was primarily focused on providing professional help, mental support, activities aimed at maintaining physical activity and independence in everyday activities, and, above all, on shaping the skills of self-control and self-care.Conclusions. Nursing care for a patient with lung cancer and co-occurring diabetes, due to the chronic aspect of both diseases, focuses mainly on taking measures to prevent complications as well as educating and motivating pro-health behaviour.